2021
DOI: 10.1002/ehf2.13647
|View full text |Cite
|
Sign up to set email alerts
|

Stress cardiomyopathy in hospitalized patients with cancer: machine learning analysis by primary malignancy type

Abstract: Aims Previous studies have shown that patients with stress (Takotsubo) cardiomyopathy (SC) and cancer have higher in‐hospital mortality than patients with SC alone. No studies have examined outcomes in patients with active cancer and SC compared to patients with active cancer without SC. We aimed to assess the potential association between primary malignancy type and SC and their shared interaction with inpatient mortality. Methods and results We analysed SC by primary malignancy type with propensity score adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Likewise, the influence of beta-blocking agents on non-cardiac mortality is not yet well understood 28. As emerged from recent research, it might be hypothesised an impact on complex and multifactorial mechanisms involving neuroendocrine axis, immune response and cell proliferation whose modulation results in positive effects in conditions commonly associated with patients with TTS such as neurological and cancer diseases 29 30…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the influence of beta-blocking agents on non-cardiac mortality is not yet well understood 28. As emerged from recent research, it might be hypothesised an impact on complex and multifactorial mechanisms involving neuroendocrine axis, immune response and cell proliferation whose modulation results in positive effects in conditions commonly associated with patients with TTS such as neurological and cancer diseases 29 30…”
Section: Discussionmentioning
confidence: 99%
“…13 The InterTAK Registry reported that the most common malignancy associated with TTS is breast cancer, followed by tumors of gastrointestinal system and then respiratory track, and so forth. 6 Javaid and colleagues 14 report the results of a large cohort study, based on a US national inpatient sample, having included 4.7 million patients hospitalized with active cancer. 14 The authors found a significant prevalence of TTS in these patients of 12%, while they further investigated the association between primary tumor type and the risk for TTS using propensity-score adjustment and machine learning.…”
mentioning
confidence: 99%
“…6 Javaid and colleagues 14 report the results of a large cohort study, based on a US national inpatient sample, having included 4.7 million patients hospitalized with active cancer. 14 The authors found a significant prevalence of TTS in these patients of 12%, while they further investigated the association between primary tumor type and the risk for TTS using propensity-score adjustment and machine learning. According to their findings, only breast and lung cancer were associated with a significantly increased likelihood of TTS.…”
mentioning
confidence: 99%
See 2 more Smart Citations